Clinical significance of changes in the expression of Toll-like receptors of type 2, 4 and 9 in the formation of secondary immune dysfunction syndrome in military personnel - N. S. Zaitseva; L. P. Sizyakinа (Медицинский вестник Юга России, 2022)
Objective: to study the dynamic changes in the content of monocytes expressing Toll-like receptors of type 2, 4 and 9 in military personnel under occupational stress. Materiasl and methods: 37 servicemen (average age 37.3±4.8 years), who participated in special operations (service in areas with an unfavorable operational situation lasting 3 months) have been examined and divided into two groups: group I included military personnel (n=27) who had clinical manifestations of an infectious process of any etiology during participation in special operations and during 6 months of observation after returning from an area with an unfavorable operational situation; the criterion for inclusion in group II of observation was the absence of manifestation of the infectious process. Phenotyping of peripheral blood monocytes was performed by flow cytofluorimetry. Statistical data processing was carried out using the STATISTICA 12 software package (StatSoft InC., USA). Results: during 6 months of follow-up, all the examined servicemen had a persistent significant decrease in the content of monocytes expressing Toll-like receptors of type 4 and no change in the content of monocytes expressing Toll-like receptors of type 9. In the group with the manifestation of the infectious syndrome, there was a significant decrease in the number of monocytes expressing Toll-like type 2 receptors, most pronounced by the 6th month of follow-up. Conclusions: violation of antigenic recognition processes at the level of innate immunity structures in military personnel within six months after participating in special operations, allows these individuals to be classified as at risk of developing persistent immune dysfunction.